Hagenberg Research - Buchberger, Bruno; Affenzeller, Michael; Ferscha, Alois; Haller, Michael; Jebelean, Tudor; Klement, Erich Peter; Paule, Peter; Pomberger, Gustav; Schreiner, Wolfgang; Stubenrauch, Robert; Wagner, Roland; Weiß, Gerhard; et al. (Springer Berlin Heidelberg : Imprint: Springer, 2009)
This book is a synopsis of the basic and applied research carried out at the various research institutions of Softwarepark Hagenberg in Austria. Started in 1987, following a decision of the government of Upper Austria to create a scientific, technological, and economic impulse for the region and for the international community, Softwarepark Hagenberg has grown in size to over 1000 R&D employees and 1300 students in six research institutions, 40 companies and 20 academic study programs at the bachelor's, master's and PhD levels. The overall goal of Softwarepark Hagenberg is economic stimulation through innovative software technologies. The contributions in this book provide an overview of current research in the field of software science and related areas pursued at the six research institutions of Softwarepark Hagenberg. The subjects addressed range from computational logic and mathematics to software science and applied technologies. The message of this book is that economic and scientific innovation can only be achieved by emphasizing basic and applied research.